Concepts Of Serious Game In Education (International Journal of Engineering and Computer Science, 2015)
using technology in Education is still very limited compare to other disciplines like medicine. In recent years ago researchers focus on serious game, because of the importance of game in learning and the enthusiasm of adults to play a game. Yet this process is in the research step. The model of a serious game shows its concepts, which is very important to match with the concepts of education. In this paper we try to suggest a model of serious game which includes most principles of an educational model. Then expose how a game can be used in education.